Hold your horses: A comparison of human laryngomalacia with analogous equine airway pathology. (February 2018) - Lawrence, Rachael J.; Butterell, Matthew J.; Constable, James D.; Daniel, Matija
Abstract: Objectives: Laryngomalacia is the most common cause of stridor in infants. Dynamic airway collapse is also a well-recognised entity in horses and an important cause of surgical veterinary intervention. We compare the aetiology, clinical features and management of human laryngomalacia with equine dynamic airway collapse. Methods: A structured review of the PubMed, the Ovid Medline and the Cochrane Collaboration databases (Cochrane Central Register of Controlled Trials, Cochrane Database of Systemic Reviews). Results: There are numerous equine conditions that cause dynamic airway collapse defined specifically by the anatomical structures involved. Axial Deviation of the Aryepiglottic Folds (ADAF) is the condition most clinically analogous to laryngomalacia in humans, and is likewise most prevalent in the immature equine airway. Both conditions are managed either conservatively, or if symptoms require it, with surgical intervention. The operative procedures performed for ADAF and laryngomalacia are technically comparable. Conclusion: Dynamic collapse of the equine larynx, especially ADAF, is clinically similar to human laryngomalacia, and both are treated in a similar fashion.